Selección Técnico Económica de Pavimentos para Urbanizaciones con Bajo Volumen de Tránsito - Calvo-Piedra, Francisco Javier (Instituto Tecnológico de Costa Rica, 2006)
The main objective of this project is to present a decision chart based on the point of view of the budget for the social interest urbanizations paving. The analysis done was about the actual information, the technical paving solutions, the use of geo-textiles, and the availability of those according to the economic possibility. The study takes in consideration the use of different riding surfaces, such as asphalt, concrete tiles, and hydraulic concrete slabs, all of them with their respective design of thicknesses to have comparative parameters. The done labor in the gathering of information and data has been arduous because there is almost no information in the country about such topics. Therefore, to obtain data and documents it was necessary to look for experts on the topic and to use documentation from Colombia and Chile. From the obtained results, drawn in the charts, one can see directly the selective application according to the parameters to use. In conclusion, generally there is a few or no national documentation that can be applied to the studied topic. However, this lack opens a window of interest to who desires to continue and develop some aspects or themes around this one that matters in this study.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción).Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2006.
Keywords: Adoquines; Losas de concreto; Geotextiles; Estudio comparativo; Rodamiento